A pseudo-two-dimensional conjugated polysquaraine: an efficient p-type polymer semiconductor for organic photovoltaics and perovskite solar cells. Issue 28 (29th June 2018) - Xiao, Qi; Wu, Fei; Han, MengMeng; Li, Zhen; Zhu, LinNa; Li, Zhong'an
Abstract : A new squaraine-based 2D conjugated polymer was developed as the donor material in polymer solar cells and dopant-free hole transporting material in inverted perovskite solar cells, reaching efficiencies of 6.35% and 18.29%, respectively. Abstract : In this paper, an efficient p-type polymer semiconductor (PASQ-IDT ) is first developed by integrating a two-dimensional (2D) structure concept into the design of squaraine-based π-conjugated polymers, and it shows multiple applications in both bulk-heterojunction polymer solar cells (BHJ-PSCs) and perovskite solar cells (PVSCs) with high performance. As the polymer-donor blended with a fullerene acceptor, PASQ-IDT can endow the derived additive-free single-junction PSCs and semi-transparent PSCs with impressive efficiencies of 6.35% and 4.03%, respectively, both of which are the highest values reported for polysquaraines. More encouragingly, PASQ-IDT not only exhibits good hole extraction/transport ability, but also shows very good surface wettability to the perovskite precursor solution to enable the growth of perovskites with high film quality, making it suitable as an efficient hole transporting material (HTM) for inverted PVSCs. Thus, a very promising efficiency of 18.29% with negligible hysteresis and good device stability can be delivered byPASQ-IDT -based inverted PVSCs in the absence of dopants, outperforming the PEDOT:PSS-based control devices (16.14%) and most dopant-free HTMs reported so far.